Validation of a technology: manual for outpatient and surgical care in sexual diversity (Research, Society and Development, 2021)
Introduction: Diversity means variety, difference. It brings together the most diverse social, cultural, and gender types-a term used to refer inclusively to all gender diversity-which are important in forming a heterogeneous community. The development of the Manual for Outpatient and Surgical Reception in Sexual Diversity provided information about sexual diversity care. Objectives: To validate an instrument entitled "Manual for Outpatient and Surgical Reception in Sexual Diversity in Marabá". Methodology: Applied educational technology research, with a quantitative and analytical approach, using 16 expert judges. The Cronbach's alpha was applied to verify the consistency of the questionnaire and statistical analysis of the data through the content validation index (CVI) to validate the manual. The research was conducted between March 05 and 20, 2021, during 15 calendar days, in the city of Marabá, Pará. Results: Cronbach's alpha was 0.937, and represents an excellent classification in the evaluation of the variances of the questions in the questionnaire applied to the judges. The CVI calculation obtained a result of 0.952, and the desirable values are between 0.76 and 1. Thus, it was established that the overall approval rating was 92.1%. Final considerations: With the results obtained, the manual of Outpatient and Surgical Reception in Sexual Diversity was considered validated, proving to be a valid instrument to support the professionals in assisting the public and the peculiarities of outpatient and surgical care in sexual diversity.